Strategi Komunikasi PT KAI Dalam Masa Pandemi Covid 19 - Intan Leliana (Jurnal Public Relations (J-PR), 2021)
Based on number SK-77/MBU/03/2020 concerning the Establishment of the National Disaster Task Force for State-Owned Enterprises, KAI was appointed as the Coordinator of the West Sumatra Region. Through this appointment, KAI coordinates with existing SOEs, as well as local BPBDs in distributing disaster assistance, especially medical equipment and other assistance related to the current Covid-19 pandemic and other natural disasters. PT KAI's concern. Efforts to prevent the spread of the virus include travel restrictions, quarantines, curfews, event delays and cancellations, and facility closures. In Indonesia, prevention efforts are implementing PSBB in some areas. PSBB stands for Large-Scale Social Restrictions, a regulation issued by the Ministry of Health (Kemenkes) in the context of the Acceleration of Handling COVID-19 so that it can be implemented immediately in various regions. This study uses a descriptive qualitative approach with news content analysis methods in several online media. After PT KAI's CSR activities run, internally it will evaluate the results of each activity. In a company, of course, already has a CSR program in developing the company's image in the eyes of the public. However, in starting CSR the company must pursue profit / profit to meet the company's operational needs. So that the determination of the goals and basis of PT KAI's CSR program is aimed at the company itself, the government and the community Keyword: CSR, Pandemic, online media